Genetic diversity of Metarhizium sp. isolated from various hosts in East Dumoga, North Sulawesi, Indonesia - PARLUHUTAN SIAHAAN; ROWLAND ERVAN RUSFANDI MANGAIS; BEIVY KOLONDAM; AGUSTINA TANGAPO; SUSAN MAMBU (Society for Indonesian Biodiversity, 2023)
Abstract. Siahaan P, Mangais RER, Kolondam B, Tangapo A, Mambu S. 2023. Genetic diversity of Metarhizium sp. isolated from various hosts in East Dumoga, North Sulawesi, Indonesia. Biodiversitas 24: 6888-6896. Metarhizium fungus is an entomopathogenic fungus known to kill many insect pests. This means that Metarhizium sp. has an important ecological role in the ecosystem, especially in controlling insect populations and recycling nutrients. Studying the genetic diversity of Metarhizium species and their relationships with insect hosts provides insight into pest management and the study of their taxonomy. The study aimed to investigate the genetic variability among Metarhizium fungi by examining their respective host types, which can be used as basic data for taxonomic studies, germplasm conservation efforts, and pest management. Exploration results showed that three insect species were infected with the Metarhizium sp fungus, namely Scotinophara coarctata, Nilaparvata lugens, and Recilia dorsalis. The results of a phylogenetic analysis has shown that the S. coarctata isolate was in the same group as four comparable Metarhizium anisopliae isolates from GenBank with a similarity level of 100%, while the N. lugens and R. dorsalis isolates were in the same group as four Metarhizium huainamdangense isolates with a similarity level. 99% and three isolates of Metarhizium flavoviride with 98% similarity. Molecular analysis confirmed that the Metarhizium isolated from S. coarctata was the M. anisopliae species, while those isolated from N. lugens and R. dorsalis were the M. huainamdangense species. Differences in host insects have been proven to provide genetic variation to the Metarhizium sp. fungus.